Treatment of Shear Stress versus Shear Rate Data for Natural Fiber Reinforced Polymer Composites: A Discussion - Begum, K.; Islam, M. A. (Journal of Scientific Research, 2019)
The rheological properties of melt jute fiber reinforced polypropylene (PP) composites were conducted at constant shear stress. The measured shear stress and shear rate data are fitted to a power law model for measuring stress-independent melt viscosity of the composites. The viscosity increased with the increase of fiber loading and decreased with the rise of temperature. The flow behavior index, n was found to decrease with the increase of fiber loading and increase with the rise of temperature. The shear stress and shear rate data collected from different specialized research journals have also been fitted to the power law model to measure the stress-independent melt viscosity and flow index as in all the previous literatures viscosity is treated as stress dependent parameter. It was found that the dependence of the viscosity and the flow index observed from previous literature data with fiber loading and temperature was quite consistent with the present study.